2021
DOI: 10.1016/j.cell.2021.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cell repertoire for recognition of evolving SARS-CoV-2 spike

Abstract: Highlights d Seven major epitopic regions of SARS-CoV-2 spike are consistently targeted by human Abs d Ab group assignment correlates with CoV binding breadth and neutralization potency d SARS-CoV-2 variants tend to escape Abs from the groups with most potent neutralizers d Intra-group Ab binding redundancy confers robustness against emerging variants

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 60 publications
5
109
0
Order By: Relevance
“…Several studies reported on the humoral response following the BNT162b2 mRNA COVID-19 vaccination and found that SARS-CoV-2 antibody titers 4 to 6 months after infection decline more slowly than in the initial months after the infection (Ebinger et al, 2021; Padoan et al, 2021; Tré-Hardy et al, 2021). At least two recent studies reported that antibodies could be detected up to 11 months after infection and provided evidence that that these antibodies originated in memory B cells, not plasmablasts(Tong et al, 2021; Turner et al, 2021a). Generation of SARS-CoV-2 memory B cells(De Gasparo et al, 2021; Schoof et al, 2020; Xu et al, 2021) is likely necessary for long-term protection since that is the mechanism by which most anti-viral vaccines work(Iwasaki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported on the humoral response following the BNT162b2 mRNA COVID-19 vaccination and found that SARS-CoV-2 antibody titers 4 to 6 months after infection decline more slowly than in the initial months after the infection (Ebinger et al, 2021; Padoan et al, 2021; Tré-Hardy et al, 2021). At least two recent studies reported that antibodies could be detected up to 11 months after infection and provided evidence that that these antibodies originated in memory B cells, not plasmablasts(Tong et al, 2021; Turner et al, 2021a). Generation of SARS-CoV-2 memory B cells(De Gasparo et al, 2021; Schoof et al, 2020; Xu et al, 2021) is likely necessary for long-term protection since that is the mechanism by which most anti-viral vaccines work(Iwasaki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the RBD is also the primary target of the neutralizing antibodies elicited by natural infection or vaccination (Box 1 ). There are three major non-overlapping antigenic sites on the RBD 52 (Fig. 2a ).…”
Section: Coronavirus S Proteinmentioning
confidence: 99%
“…However, the widespread emergence of viral variants that evade neutralization by preformed antibodies present in convalescent serum will likely significantly decrease the duration of antibody-mediated immunity elicited by SARS-CoV-2 infection 74 , 75 . In these cases, protection against severe disease will be reliant on the reactivation of somatically mutated memory B cells that recognize antigenically distinct viral variants, which is discussed further in the next section 40 , 76 , 77 .…”
Section: B Cell Response To Sars-cov-2 Infectionmentioning
confidence: 99%